Fostering nationalism through digital poetry: A design-based study integrating constructivist and culturally responsive pedagogy in Indonesian elementary educationducation - Pamungkas, Onok Yayang; Sisdiana, Etty; Widaryanto, Benny; Jarwadi; Agung, Iskandar; Siswayanti, Novita; Syukri, Agus Fanar (Research Journal in Advanced Humanities, 2025)
This study examines the effectiveness of a digital poetry-based learning application, SENANDI (Seni dan Nasionalisme Digital), in fostering nationalism among elementary school students in Yogyakarta, Indonesia. Employing a design-based research (DBR) approach, the study integrated constructivist principles, the Technological Pedagogical Content Knowledge (TPACK) framework, and culturally responsive pedagogy across three iterative phases: design, expert validation, and empirical testing. Seventy-eight fourth-grade students participated in an eight-week intervention using the SENANDI platform. Quantitative results from a one-group pretest–posttest design revealed significant improvement in students’ nationalism attitudes (Cohen’s d = 1.43), with the highest gains observed in cultural appreciation (d = 1.52). Regression analysis indicated that the quality of poetry produced by students was the strongest predictor of nationalism gains (β = .45, p < .001), suggesting that creative depth contributes more meaningfully to value internalization than usage frequency. These findings highlight the pedagogical potential of creative digital tools to promote civic and character education, particularly when embedded in culturally grounded learning contexts. The study concludes that technology-mediated creative expression can serve as a transformative means of instilling national values in primary education.